Slow growth and unstable ribosomal RNA lacking pseudouridine in mouse embryonic fibroblast cells expressing catalytically inactive dyskerin. Issue 14 (28th May 2013) - Gu, Bai-Wei; Ge, Jingping; Fan, Jian-Meng; Bessler, Monica; Mason, Philip J.
Abstract : Pseudouridine is the most abundant modified nucleotide in ribosomal RNA throughout eukaryotes and archaea but its role is not known. Here we produced mouse embryonic fibroblast cells expressing only catalytically inactive dyskerin, the pseudouridine synthase that converts uridine to pseudouridine in ribosomal RNA. The mutant dyskerin protein, D125A, was extremely unstable but cells were able to divide and grow very slowly. Abnormalities in ribosome RNA synthesis were apparent but mature cytoplasmic RNAs lacking pseudouridine were produced and were very unstable. We conclude that pseudouridine is required to stabilize the secondary structure of ribosomal RNA that is essential for its function. Abstract : MEF cells with a mutant dyskerin have no detectable pseudouridine in ribosomal RNA. Catalytically null mutant dyskerin D125A is very unstable. Pseudouridine is important in rRNA processing in IVS1. Pseudouridine is important for ribosomal RNA stability. Pseudouridine stabilizes the functional secondary structure of RNA.